Recommendations for extracorporeal cardiopulmonary resuscitation (eCPR): consensus statement of DGIIN, DGK, DGTHG, DGfK, DGNI, DGAI, DIVI and GRC - Michels, Guido; Wengenmayer, Tobias; Hagl, Christian; Dohmen, Christian; Böttiger, Bernd W.; Bauersachs, Johann; Markewitz, Andreas; Bauer, Adrian; Gräsner, Jan-Thorsten; Pfister, Roman; Ghanem, Alexander; Busch, Hans-Jörg; et al. (Clinical research in cardiology, 2019)
Extracorporeal cardiopulmonary resuscitation (eCPR) may be considered as a rescue attempt for highly selected patients with refractory cardiac arrest and potentially reversible aetiology. Currently, there are no randomised, controlled studies on eCPR. Thus, prospective validated predictors of benefit and outcome are lacking. Currently, selection criteria and procedure techniques differ across hospitals and standardised algorithms are lacking. Based on expert opinion, the present consensus statement provides a first standardised treatment algorithm for eCPR.
Published online: 04 September 2018
Gesehen am 24.03.2020